QTL Analysis in Sorghum (Sorghum bicolor L. Moench): A Review - Fawwaz Dinanty; Fathur Rachman (Universitas Atma Jaya Yogyakarta, 2026)
Sorghum is a Gramineae crop with two sets of chromosomes (2n = 2x = 20). Sorghum has a euchromatin and heterochromatin size of about 252 Mbp and 460 Mbp, respectively. QTL analysis determines the region in the genome that controls a quantitative character phenotype. The methods of analysis include SMA, SIM, CIM, and MQM. Genotyping generally uses molecular markers with a high polymorphism, such as RFLP, AFLP, SSR, SNP, and DArT. QTL analysis has been conducted on sorghum crops for various purposes and traits. The analyzed agronomic traits were plant height, days to flowering, 1000 grain weight, and seed length. The grain quality, including mineral content (Fe and Zn), starch, fat, fibre, protein, and carotenoid content, can be analyzed. Disease resistance that can be analyzed is resistance to leaf spot and anthracnose. Several QTLs were co-localized between traits and between populations. The data that has been obtained can be used for the preparation of the QTL consensus.